Membangun Karakter Kristen: Peran Kompetensi Profesional Guru Pendidikan Agama Kristen - Sitanggang, Anggita Anggraini; Naibaho, Dorlan (Jurnal Pendidikan Non formal, 2023)
Successful education is not limited to providing knowledge or information alone, but is able to bridge behavioral transformations in each individual. The success of education lies in its ability to shape a person's character, attitudes, and morals. More than just knowledge transfer, quality education provides a strong foundation for positive personality development. A teacher who is classified as a professional is a role model for his students, but if we look at the reality, there are still many unprofessional teachers who maintain bad behavior. This study aims to explore the relationship between teacher professional competence and Christian character building in the context of Christian religious education. The research approach applied is qualitative through a literature review method. The results showed that a teacher needs to master all the basic competencies of the teacher, including spiritual competence to be an example for students in forming Christian character. The implication is the teacher's contribution to Christian education that is relevant to the demands of the times. This research provides a deeper understanding of the essential relationship between teachers' professional competence and Christian character building, enriching the context of Christian religious education.